2018
DOI: 10.18733/cpi29363
|View full text |Cite
|
Sign up to set email alerts
|

The Open Studio: Exploring Immigrant and Refugee Youth Experiences of Belonging through Community-Based Arts Practice

Abstract: The Open Studio is a publicly accessible art-making space grounded in ideals of collaborative community development, Adlerian theory, social justice, and feminist thoughts. Our project involved visual art-making and exploring high school immigrant students’ experiences of inclusion and belonging. The purpose was to help immigrant and refugee youth to adapt to a city in Newfoundland, where newcomers often face an insider/outsider dynamic of disconnection. The Open Studio was structured along seven parameters: f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…We (Lewis et al, 2018) draw connections with these tenets of community psychology and arts practice, as falling neatly in agreement with the Crucial Cs framework (Bettner & Lew, 1999). These frameworks provide tools for fostering community engagement and attachment, collaboratively moving towards defined senses of efficacy, and empowerment experiences through resilience and hope.…”
Section: Hope and Resilience In Community Practicementioning
confidence: 69%
See 1 more Smart Citation
“…We (Lewis et al, 2018) draw connections with these tenets of community psychology and arts practice, as falling neatly in agreement with the Crucial Cs framework (Bettner & Lew, 1999). These frameworks provide tools for fostering community engagement and attachment, collaboratively moving towards defined senses of efficacy, and empowerment experiences through resilience and hope.…”
Section: Hope and Resilience In Community Practicementioning
confidence: 69%
“…This focus group added the youths' perspective on the concept of hope related to their newcomer experiences and the Art Hive. We focused on hope in part due to our first stage of data collection, which indicated that the Art Hive itself was a non-evaluative location for social engagement and a site for connecting with new friends (Lewis et al, 2018). Additionally, the youths' interpersonal engagement increased through the surfacing of all four of Bettner and Lew's Crucial C framework (1999).…”
Section: Situating Arts-based-research In Communitiesmentioning
confidence: 99%
“…This question reveals a whole spectrum of discussed issues about the failures of integration schemes, frameworks and plans. Many studies show that belonging to art-related communities strengthens the integration process and helps migrant children to adapt in new communities (Lewis, McLeod, Li 2018;Lundberg 2016;Quadros, Vu 2017;balfour, bundy, burton, Dunn, Woodrow 2015;Rothchild 2015). our respondents did not expressly name the fruitfulness of such activities, however, we noticed that hard-working and talented children from migrant communities have an indisputable impact on class and school society, and the expression of artistic talents help them in terms of accommodation.…”
Section: Discussionmentioning
confidence: 99%
“…Community development activities are usually discussed under community development projects in migration and refugee studies. They take different forms ranging from sport activities (Nathan et al, 2010;Rosso and McGrath, 2016;Mohammadi, 2019;Robinson et al, 2019) to art activities (Lewis et al, 2018;Nashwan et al, 2019;Lee et al, 2020). Community engagement activities are one important aspect of social cohesion programs, which have been implemented in all countries under investigation, namely, Turkey, Lebanon, and Jordan.…”
Section: Community Engagement: Constructing Shared Spacesmentioning
confidence: 99%